KETERWAKILAN PEREMPUAN SEBAGAI PENGAWAS PEMILU PADA PILKADA PROVINSI LAMPUNG 2018 DI KABUPATEN PRINGSEWU - Syarifudin, Ahmad; Malik, Adam (Center of Gender Studies and Child of State Islamic Institute of Metro, 2021)
Women’s representation as supervisor of regional election doesn’t have a legal basis in Law No. 6 Year 2020. Thus in regional election 2024 supervisor have the potential to be recruited without considering women’s representation. This research seek to reflect supervisor in the regional election Lampung Province 2018 in Pringsewu Regency and project the implementation of the regional election Lampung Province 2024 in Pringsewu Regency. Therefore, this study proposes 2 problem formulations, namely: 1) how is the representation of women as supervisor of regional election Lampung Province 2018 in Pringsewu Regency? 2) What is member Supervisory Body’s view to women representation in Regional Election Lampung Province 2018 in Pringsewu Regency? This is qualitative research using primary data collect by interviews, and secondary data using documentation and literature study. The conclusion are: 1) women’s representation in regional election Lampung Province 2018 in Pringsewu Regency under 30% (thirty percent) for Panwaslu Kecamatan (7,4%) and Panwaslu Desa (9,16%). But for Pengawas TPS got above 30% (thirty percent). 2) Supervisory Body Pringsewu Regency try to increase the representation of women as supervisor by cooperating with women organization and intensive socialization.